Studies on Neotropical crickets: A new Anurogryllina genus (Orthoptera: Gryllidae: Gryllinae) - Cadena-Castañeda, Oscar J.; Vásquez Rodríguez, Martha Carolina; Gonzalez, Gloria Raquel Dávila; López, Víctor Hugo Grande (Zootaxa, 2021)
Andeogryllus n. gen. including two new species from the inter-Andean slopes and valleys of the Magdalena and Cauca rivers of Colombia are described. This new genus is similar to Zebragryllus in their habitus, differed by not have white stripes on the body or antennae and by a modified pseudoepiphallic sclerite. The genus Atsigryllus (Atsigryllae group) is located in the subtribe Anurogryllina, highlighting the secondary reduction of the median lobe. An updated key is provided for the genera of the subtribe Anurogryllina and the species of the new genus.